Fostering Sustainable Development in the Age of Technologies - Sharma, Rohit (Emerald Publishing Limited, 2023)
Fostering Sustainable Development in the Age of Technologieshighlights the interplay between various disruptive technologies such as Artificial Intelligence, Autonomous robots, Big Data Analytics, Blockchain, Cloud Computing, and Digital Twins, and holistic sustainable development
Description based on publisher supplied metadata and other sources
Keywords: Sustainable development